Średniowieczne kabłączki skroniowe z pozostałościami nitek z Łowicza, woj. łódzkie - Antosik, Łukasz; Słomska, Joanna; Zawilski, Paweł (Acta Universitatis Lodziensis. Folia Archaeologica, 2019)
In 2011, an archaeological supervision was carried out in the town of Łowicz, related to construction works. In the course of works, a small number of artefacts was found, dated to the late Middle Ages and the early modern period. The most interesting find is a group of 9 temple rings deposited in the excavation unit no. III, upon which organic remains of textile products were found. The discovered decorative artefacts are temple rings representing the type III according to the classification by K. Musianowicz or the variant B according to the classification by H. Kóčkę-Krenz. The textile remains have been preserved in residual form on six out of nine temple rings. These are small fragments of threads and remains of mineralized fibres. On four artefacts, both thread and fibre parts were visible. All thread fragments were produced of plant fibre, most probably, the universally employed linen. The threads are Z-twisted, the twist being very weak. The state of preservation of other fibres surviving on the surface of the temple rings was too poor to enable detailed technological analyses. The described temple rings were most probably originally deposited in a grave that was destroyed in unknown circumstances. It can be stated that the textile evidence does not differ from other finds of this type from the discussed period.